(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
The work with clay traditionally developed by artisans and potters in the Baixo Jaguaribe Region, in Ceará, underwent profound transformations from the 1960s onwards by incorporating the use of machinery. The old potteries gave way to tile and brick factories that increased the demand for raw materials and labor, attracting subjects from other cities in Ceará and neighboring states in search of job opportunities. Using demographic censuses and oral sources, the objective of this article is to investigate the trajectories of these workers, analyzing the process of proletarianization that reaches these subjects when they become workers, inserting themselves in the factory logic and distancing themselves from agriculture and peasant life. Keywords: Sertanejo. Ceramic activity. Proletarianization.